1999
DOI: 10.2500/108854199778339053
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Allergic Rhinitis

Abstract: With unfortunate high frequency, clinicians consider allergic rhinitis to be more of a nuisance than an illness. When in fact, allergic rhinitis is not only a very common disease process, affecting up to a cumulative frequency of 42% of the U.S. population by age 40, but can lead to significant short-term and long-term medical complications. Poorly controlled symptoms of allergic rhinitis may contribute to sleep loss, secondary daytime fatigue, learning impairment, decreased overall cognitive functioning, decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 0 publications
0
63
0
1
Order By: Relevance
“…5 Furthermore, if left untreated, allergic rhinitis can potentially exacerbate and contribute to asthma 6 as well as other comorbidities such as conjunctivitis, otitis, dental malocclusions, sinusitis, respiratory infections, and learning problems. [7][8][9][10][11][12] Antihistamines have been a valuable allergic rhinitis treatment for decades, and data from studies in adult populations have been widely reported. Although some studies have assessed symptom relief of SAR in children using antihistamines, [13][14][15][16][17][18] including a postmarketing surveillance program, 19 only one study 13 has used the same end points as assessed in adult clinical studies.…”
mentioning
confidence: 99%
“…5 Furthermore, if left untreated, allergic rhinitis can potentially exacerbate and contribute to asthma 6 as well as other comorbidities such as conjunctivitis, otitis, dental malocclusions, sinusitis, respiratory infections, and learning problems. [7][8][9][10][11][12] Antihistamines have been a valuable allergic rhinitis treatment for decades, and data from studies in adult populations have been widely reported. Although some studies have assessed symptom relief of SAR in children using antihistamines, [13][14][15][16][17][18] including a postmarketing surveillance program, 19 only one study 13 has used the same end points as assessed in adult clinical studies.…”
mentioning
confidence: 99%
“…(33) Sinusitis is also one of the associated diseases and contributors to allergic rhinitis. (8,34) The commonest allergen implicated is house dust mite (HDM) which may be the worldwide commonest cause of allergic rhinitis. (35) One example to the importance of (HDM) in respiratory allergens is that the incidence of the atopy in southern France is 30% but the prevalence of allergic asthma and rhinitis is greater in the low land compared to the ALPS.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Allergic rhinitis also leads to school absenteeism and may be associated with depression, anxiety, and family dysfunction. 7,14 QOL is further reduced by headaches, altered or decreased sense of taste and smell, and embarrassing sneezing episodes at school or social functions.…”
Section: Effect Of Allergic Rhinitis On Quality Of Lifementioning
confidence: 99%